Personal Protective Equipment and Donning and Doffing Techniques in the Cardiac Catheterization Laboratory During the COVID-19 Pandemic: Insights From an Internet Search for Protocols - Haloot, Justin; Sheikh, Omar; Dollar, Fatima; Javeri, Heta; Fichardt, Hendre Jeannetta; Fernandes, Gail; Garcia, Marlene; Prasad, Anand (Frontiers in Cardiovascular Medicine, 2021)
Background: Due to the ongoing COVID-19 pandemic, a need for precise donning and doffing protocols for personal protective equipment (PPE) amongst healthcare infrastructures is paramount. Procedures involving the cardiac catheterization laboratory (CCL) are routinely non-aerosolizing but have the potential for rapid patient deterioration creating the need for aerosolizing generating procedures. Multiple societal and governmental guidelines on the use of PPE during medical procedures are available on internet websites, however there is limited literature available in peer reviewed formats in this context. This study aims to provide an overview of current PPE donning and doffing protocols specific to the catheterization laboratory. Methods: A series of internet searches regarding donning and doffing of PPE in the CCL including published articles and internet protocols were compiled and compared using Pubmed.gov, Google.com, Twitter.com, and Youtube.com. Results: Most institutions used N95 masks, shoe covers, at least one head covering, face shield or goggles, two pairs of gloves and inner and outer gowns. Doffing variation was greater than donning. Doffing has the potential to contaminate the HCW and therefore this step of PPE management requires further study. Common steps in temporal priority included cleaning of gloved hands, removal of outer (or only) gown, removal of outer gloves, repeat gloved hand cleaning, removal of facial PPE last, and a final non-gloved hand cleaning. Conclusions: This analysis provides a summary of commonly used practices that may be considered when designing a CCL specific PPE protocols. Analysis of consistent steps from the literature led the authors to formulate a suggested protocol for CCL HCWs when performing procedures on patients with confirmed or suspected/unknown COVID-19.